In vivo study of teratogenic and anticonvulsant effects of antiepileptics drugs in zebrafish embryo and larvae - Martinez, Carolina Soledad (2018)
Epilepsy is a neurological disorder treated with antiepileptic drugs (AEDs). Since AEDs are administered in women in childbearing age, it is critical to study if drugs are capable of inducing developmental toxicity. Along the bibliography available, there is no research comparing teratogenicity and anticonvulsant effect within the same study. In the present study, we evaluated the teratogenic and anticonvulsant effects of six different AEDs: carbamazepine, levetiracetam, lamotrigine, phenobarbital, phenytoin and valproic acid. Zebrafish was the selected animal model because of its small size, rapid external development and similar neurophysiology to mammals. Zebrafish embryo and larvae were exposed to AEDs. Embryo development was monitored by their hatching and morphology. In larvae, locomotor activity was measured as a parameter of neurotoxicity. Finally, anticonvulsant effect was determined after exposure to AEDs in zebrafish larvae treated with the proconvulsant drug pentylenetetrazole. Our results suggest that lamotrigine and phenytoin could be suitable non-teratogenic and efficient anticonvulsant options for epilepsy treatment.